Single-Cell Sequencing Unveils the Heterogeneity of Nonimmune Cells in Chronic Apical Periodontitis - Lin, Xinwei; Chi, Danlu; Meng, Qingzhen; Gong, Qimei; Tong, Zhongchun (Frontiers in Cell and Developmental Biology, 2022)
Chronic apical periodontitis (CAP) is a unique dynamic interaction between microbial invasions and host defense mechanisms, resulting in infiltration of immune cells, bone absorption and periapical granuloma formation. To help to understand periapical tissue pathophysiology, we constituted a single-cell atlas for 26,737 high-quality cells from inflammatory periapical tissue, and uncovered the complex cellular landscape. The eight types of cells, including nonimmune cells and immune cells, were identified in periapical tissue of CAP. Considering the key roles of nonimmune cells in CAP, we emphasized osteo-like cells, basal/stromal cells, endothelial cells and epithelial cells, and discovered their diversity and heterogeneity. The temporal profiling of genomic alterations from common CAP to typical periapical granuloma provided predictions for transcription factors and biological processes. Our study presented potential clues that the shift of inflammatory cytokines, chemokines, proteases and growth factors initiated polymorphic cell differentiation, lymphangiogenesis and angiogenesis during CAP.